Pengaruh Kecerdasan Emosional, Kecerdasan Spritual, dan Disiplin Kerja terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Sleman - Dwi Lestari; Nany Noor Kurniyati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to examine the influence of emotional intelligence, spiritual intelligence, and work discipline on the performance of employees at the Sleman Regency DPRD Secretariat. The specific objectives are: (1) to analyze the partial effect of the three variables on employee performance, (2) to assess their simultaneous effect, (3) to determine the magnitude of their contribution to performance, and (4) to identify the level of simultaneous influence on employee performance. This research employs a quantitative descriptive approach and was conducted at the Sleman Regency DPRD Secretariat Office, Yogyakarta Special Region. The research sample consisted of 33 civil servants selected using purposive sampling. Data were collected through questionnaires tested for validity using Pearson product moment correlation and for reliability using Cronbach’s Alpha, showing that all instruments were valid and reliable. The analysis included normality, linearity, multicollinearity, and heteroscedasticity tests, along with t-tests, multiple linear regression, F-tests, and the coefficient of determination. The findings indicate that emotional intelligence and spiritual intelligence do not have a significant partial effect on performance (Sig. > 0.05), but they do show a significant simultaneous effect (Sig. < 0.05). Their overall contribution to performance is 54.8%, with a simultaneous influence level of 54.1%, categorized as moderate. Thus, emotional and spiritual intelligence collectively influence employee performance at the Sleman Regency DPRD Secretariat.